BELAJAR BERSAMA PARA JAMAAH DI PERPUSTAKAAN MASJID - Rosfiantika, Evi; Yusup, Pawit M (Universitas Padjadjaran, 2015)
The mosque is a place of worship for Muslims, both in nature mahdoh and ghoerumahdhoh. In the context of worship latter, very broad and diverses, one of which is a mosque used as a place of activities for the benefit of mankind. One of the activities is to build mosque to learn add to the general knowledge and religious through reading. Means and facilities for reading in mosque activities carried out by the Mosque Library. These activities are not directly become binding pilgrims to stay longer while reading in the library of the mosque. One example of such activities include: (1) discussion and shared learning and reading and its implications for the intellectual development of Muslims in general; (2) the provision of facilities books and other media that are useful; (3) The activities of assistance to pilgrims in learning and reading according to their specialization.Masjid adalah tempat ibadah bagi Muslim, baik di alam mahdoh dan ghoerumahdhoh. Dalam konteks penyembahan kedua, dan diverses sangat luas, salah satu yang adalah sebuah masjid digunakan sebagai tempat kegiatan-kegiatan untuk kepentingan manusia. Salah satu kegiatan adalah untuk membangun masjid untuk mempelajari menambahkan ke pengetahuan umum dan melalui agama membaca. Berarti fasilitas dan untuk membaca masjid di kegiatan yang dilakukan oleh Perpustakaan Masjid. Kegiatan ini tidak langsung menjadi mengikat peziarah untuk tinggal lebih lama di saat membaca di perpustakaan masjid. Salah satu contoh dari kegiatan-kegiatan seperti ini mencakup: (1) diskusi dan belajar bersama dan membaca dan implikasi untuk perkembangan intelektual Muslim secara umum; (2) penyediaan fasilitas buku dan media lain yang berguna; (3) aktiviti-aktiviti bantuan kepada peziarah dalam pembelajaran dan membaca menurut spesialisasi mereka.